2004
DOI: 10.1080/00150190490462531
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Multisite Correlations in Disordered Structures

Abstract: Monte Carlo simulation modelling techniques are used to demonstrate that in two example systems the observed highly structured diffuse scattering can be explained in terms of a simple model involving a multi-site interaction originating from a local crystal chemistry constraint. The two examples discussed involve O/F ordering in K 3 MoO 3 F 3 and Bi/Zn cation ordering in the cubic pyrochlore (Bi 1.5 Zn 0.5 )(Zn 0.5 Nb 0.5 )O 7 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…See [81] for details. In later works Welberry and Goossens [84,85] and Welberry [86] have shown that the same local structure picture as delivered by Paściak et al, with domains filling the whole simulated system, can be obtained with models which make use of multi-site correlations [87] that lead to the appearance of properly oriented domain walls. At the same time they showed that the domains should remain essentially two-dimensional to better fit the experimental data.…”
Section: Monte Carlo Modelingmentioning
confidence: 79%
“…See [81] for details. In later works Welberry and Goossens [84,85] and Welberry [86] have shown that the same local structure picture as delivered by Paściak et al, with domains filling the whole simulated system, can be obtained with models which make use of multi-site correlations [87] that lead to the appearance of properly oriented domain walls. At the same time they showed that the domains should remain essentially two-dimensional to better fit the experimental data.…”
Section: Monte Carlo Modelingmentioning
confidence: 79%
“…In this respect, although to a first approximation the system can be considered as an array of interacting dipoles, this is not sufficient. In order to induce planar interfaces, which are clearly of great importance, the type of multi-site interactions that derive directly from the chemistry and that are crucial in understanding many solid-state chemical systems (Welberry, 2004) could provide the key to understanding these important materials. Work along these lines is planned.…”
Section: Resultsmentioning
confidence: 99%
“…Welberry, 2004) which usually arises from relatively simple local crystal chemical considerations and can often be relatively easily understood (see e.g. Brunel et al, 1972;Parthé, 1972, 1974;de Ridder et al, 1976ade Ridder et al, , b, 1977aWithers et al, 2003aWithers et al, , 2004b.…”
Section: The Shape Of the Observed Diffuse Distributionmentioning
confidence: 99%